Valproic Acid Attenuates Traumatic Brain Injury-Induced Inflammation in Vivo: Involvement of Autophagy and the Nrf2/ARE Signaling Pathway - Chen, Xiangrong; Wang, Handong; Zhou, Mengliang; Li, Xiang; Fang, Zhongning; Gao, Hongzhi; Li, Yasong; Hu, Weipeng (Frontiers in Molecular Neuroscience, 2018)
Microglial activation and the inflammatory response in the central nervous system (CNS) play important roles in secondary damage after traumatic brain injury (TBI). Transcriptional activation of genes that limit secondary damage to the CNS are mediated by a cis-acting element called the antioxidant responsive element (ARE). ARE is known to associate with the transcription factor NF-E2-related factor 2 (Nrf2), a transcription factor that is associated with histone deacetylases (HDACs). This pathway, known as the Nrf2/ARE pathway, is a critical antioxidative factor pathway that regulates the balance of oxygen free radicals and the inflammatory response, and is also related to autophagic activities. Although valproic acid (VPA) is known to inhibit HDACs, it is unclear whether VPA plays a role in the microglia-mediated neuroinflammatory response after TBI via regulating oxidative stress and autophagy induced by the Nrf2/ARE signaling pathway. In this study, we demonstrate that microglial activation, oxidative stress, autophagy, and the Nrf2/ARE signaling pathway play essential roles in secondary injury following TBI. Treatment with VPA alleviated TBI-induced secondary brain injury, including neurological deficits, cerebral edema, and neuronal apoptosis. Moreover, VPA treatment upregulated the occurrence of autophagy and Nrf2/ARE pathway activity after TBI, and there was an increase in H3, H4 histone acetylation levels, accompanied by decreased transcriptional activity of the HDAC3 promoter in cortical lesions. These results suggest that VPA-mediated up-regulation of autophagy and antioxidative responses are likely due to increased activation of Nrf2/ARE pathway, through direct inhibition of HDAC3. This inhibition further reduces TBI-induced microglial activation and the subsequent inflammatory response, ultimately leading to neuroprotection.